The Culture of Royal Member’s Marriage in The Novel of Only a Promise by Marry Balogh - Celincia Aniva Lebia Dos Reis (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2026)
This research is entitled The Culture of Royal Weddings in the Novel Only a Promise by Mary Balogh. It aims to examine the wedding culture of royal family members as represented in the novel through an analysis of intrinsic literary elements, namely plot, setting, character, and point of view. This study employs a qualitative descriptive research method by analyzing data derived from each intrinsic element. The research focuses on the literary work itself; therefore, an objective approach is applied. The findings indicate that nine aspects of wedding culture are depicted in the novel: seeking blessings, royal family discussions, public announcements, wedding preparations, wedding ceremonies, grand wedding celebrations, information dissemination, the acquisition of titles, and the perception of marriage as a social duty. Keywords: The Culture, The Wedding, Royal members, Intrinsic Elements